Contribution of friction-induced vibration to the realistic failure analysis of spur gear cracked teeth - Omran Abdallah (17823458) (2024)
A cracked tooth is a common occurrence in gears. However, the dynamic behavior of gears with cracks and poor lubrication that leads to rubbing between the teeth is poorly understood, limiting the reliability and precision of gear transmission. This article proposes a comprehensive model for studying the dynamic behavior of a one-stage spur gearbox with cracked teeth under poor lubrication conditions. The inter-teeth rubbing generated by the sliding of one surface relative to another is caused by the variation in the curvature radii of both mating teeth when the contact point moves along the line of contact. In addition, under the load transmitted between the mating teeth, the common elastic deformed area, computed by Hertz's theory, also varies, generating noise with modulated and constant amplitudes. Adding this friction-induced noisy vibration to the impulsive periodic response was found to realistically mimic natural behavior experimentally measured on a test rig specially developed for this investigation. According to the time-domain statistical indicators, the study concluded that the combination of both components of friction-induced noise and the primary impacting response was found to accurately and realistically simulate the dynamic behavior of the gearbox. Other Information Published in: Engineering Failure Analysis License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.engfailanal.2024.107956